Por que aprender isso, professora? Sentido pessoal e atividade de estudo na Psicologia Histórico-Cultural - Asbahr, Flávia da Silva Ferreira [UNESP]; de Souza, Marilene Proença Rebello (My University, 2014)
This research investigated the process of personal sense attribution to the study activity of students in Elementary School. The theoretical reference is the Historical-Cultural Psychology. It was conducted with students from 4th grade in a public school. The methodological procedures were: observation the daily life of a classroom; learning oriented situations; focus groups; interviews. As a result, we sought to define the analysis unit: the relation between the study activity motives and the objectives of study actions. It is defended the thesis that for the scholar learning to happen, the study actions of the students must have a personal sense correspondent to the motives and to the social meanings of the study activity, towards the human development promotion.
Why do I need lo learn this, teacher? Personal sense and study activity in historic-cultural Psychology
Keywords: Fundamental education; Historic-cultural psychology; School activity